The effect of training program on Autism Spectrum Quotient scores - Hossein Nazary Sharif; Sarvin Salar; Justin Haegele (Sport Sciences and Health Research)
Background: Autism Spectrum Quotient (AQ) functions as an evaluative instrument designed to assess traits associated with autism. Variances exist within the brain of individuals on the autism spectrum. Moreover, certain exercises have the potential to impact specific regions of the brain. Aim: This study aims to investigate how the program training of this study impact Autism—Spectrum Quotient. Materials and Methods: Forty-two children aged 7-10 years with ASD were recruited to participate in this study. These children were randomly divided into two groups: the control group (N=10, 7.80±1.35 years) and the experimental group (N=32, age: 8.16±1.16 years). The experimental group underwent an 8-week training program. The Autism Spectrum Quotient (ASQ) questionnaire was used to assess the participants' scores in the pretest and posttest. This questionnaire consists of five subscales: social skills, attention switching, attention to details, communication, and imagination, as well as a total score. Results: Based on the results, the program training had an impact on attention to detail (P=0.017) and social skills (P=0.057). However, there was no significant difference between the pretest and posttest scores for attention switching (P=0.096), communication (P=0.07), and imagination (P=0.161). Conclusion: Based on the results, we can conclude that the program had a small but significant effect in terms of quantity. Due to the specific and unique structure of the brain, it takes time to achieve a substantial impact.